Analisis Peran DPRD dalam Perencanaan dan Evaluasi Kinerja Pembangunan Daerah pada Kota Kendari - Rusiahwati Abunawas; Abd Azis Muthalib; Muh Nur; Rince Tambunan (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
This study aims to determine the role of DPRD in planning and evaluating regional development performance in South Sulawesi Province. The method used in this study is qualitative descriptive method. The methods carried out in collecting data in this study are interviews and documentation. To test the validity of the data, in this study a triangulation method was used so that the data produced was valid data for research. Data analysis techniques are data analysis with several parts, namely data collection, data reduction, data presentation, and conclusion drawing or verification. The results of data analysis show that the role of the DPRD in regional development planning in Kendari City is to compile and discuss the APBD budget, the preparation of local government work plans (RKPD) which functions as the implementation of development, MUSRENBANG starts from the Village, District and Regency levels. The role of the DPRD in evaluating the performance of regional development in Kendari City has been carried out in accordance with procedures, the findings and evaluation of the DPRD revealed that regional development in Kendari City has been in accordance with the target to be achieved in terms of economic growth and infrastructure development